Diagnostic Value of Serum Semaphorin-3A and Cartilage Oligomeric Matrix Protein in Rheumatoid Arthritis - Sarah Abbas Obaid (Newinera Publisher, 2026)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disorder characterized by persistent synovial inflammation and progressive joint damage. The identification of reliable circulating markers could potentially improve early detection of the disease. To evaluate the diagnostic potential of circulating levels of Semaphorin-3A (SEMA3A) and Cartilage Oligomeric Matrix Protein (COMP) and their combined diagnostic potential in patients with Rheumatoid Arthritis. Comparative case-control study design was conducted in Division of Rheumatology, in Al-Najaf Teaching Hospital in Al-Najaf city of Iraq, for the period between July 2025 and January 2026, included 90 participants 45 of them patients with Rheumatoid Arthritis according to ACR/EULAR criteria and 45 apparently healthy controls. Blood samples were collected from all participants, and levels of circulating SEMA3A and COMP were estimated by Enzyme-Linked Immunosorbent Assay (ELISA). The serum concentration of both COMP and SEMA3A was significantly reduced (P < 0.001) in RA patients compared with controls (7.82 ± 2.31 pg/mL and 5.41 ± 1.62 ng/mL) vs. (11.96 ± 3.04 pg/mL and 8.73 ± 2.07 ng/mL). ROC analysis showed a good degree of discrimination for SEMA3A (84%, 80%, AUC = 0.88) and COMP (80%, 76%, AUC = 0.85) in RA patients. Combination of both biomarkers resulted in a better discrimination power (88.9%, 84.4%, AUC = 0.92). Serum SEMA3A and COMP show a good degree of discrimination for RA, and the combination of both biomarkers shows a better discrimination power for the diagnosis of RA.